2013
DOI: 10.1001/jamafacial.2013.1275
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Evaluation of the Vertical Face-lift in Cadavers

Abstract: arly face-lift surgery involved excision and redraping of lax skin. 1 Results were encouraging but often short-lived and not ideal because of widening of scars and other shortfalls. Skin-only techniques were the standard surgery for the aging face until 1968, when Tord Skoog, 2 of Sweden, realized the importance of repositioning the deeper structures of the face by shifting the platysma in the neck and lower face and the fascia in the cheek. The concept of incorporating the superficial musculoaponeurotic syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…These findings are corroborated by data demonstrating similar effects in traditional SMAS plication techniques. 5 The opposing force created by midline platysmaplasty may compromise the aesthetic outcomes of rhytidectomy in 3 aspects, as represented by our data. First, it prevents vertical restoration of the cheek fat pad to its native youthful position, a hallmark of deep-plane rhytidectomy.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These findings are corroborated by data demonstrating similar effects in traditional SMAS plication techniques. 5 The opposing force created by midline platysmaplasty may compromise the aesthetic outcomes of rhytidectomy in 3 aspects, as represented by our data. First, it prevents vertical restoration of the cheek fat pad to its native youthful position, a hallmark of deep-plane rhytidectomy.…”
Section: Discussionmentioning
confidence: 70%
“…This reduces the amount of upward mobility of the jawline and neck tissues, and therefore decreases the effectiveness of treatment. 5 These undesireable outcomes perpetuate a substantial revision rate 6 and remain difficult to correct, warranting a thoughtful reevaluation of our indications for midline platysmaplasty to optimize our outcomes in the neck.…”
Section: The Effect Of Midline Corset Platysmaplasty On Degree Of Facmentioning
confidence: 99%
“…While the vertical elevation has been previously shown to have advantages in cadaver measurements, ours is the first study to compare standard deep plane entry point tissue movement to high-SMAS entry point tissue movement. [11][12][13] The high-SMAS entry for the deep plane lift above the zygomatic arch, rather than a subzygomatic diagonal one, allows for much improved vertical movement in the tissue. If a standard diagonal entry point is utilized, attempting significant vertical movement will often result in nonaesthetic skin bunching in the lateral orbital area.…”
Section: Discussionmentioning
confidence: 99%
“…While platysmaplasty provided a "hammock" or "corset" effect across the neck, it was also noted to work against and limit the upward and lateral pull on the neck associated with the traditional superolateral vectors of pull on the cheek SMAS above the mandibular line. 31,32 This tug-of-war between the downward and medial pull of platysma plication at the midline neck, and the upward and lateral pull on the SMAS has been noted to be counterproductive and to potentially limit the surgical results. Surgeons have at times turned to myotomy to more fully separate the platysmal fibers at the junction of the mandibular line and the neck to improve the appearance of the neck by creating a more visible transition from the mandibular line to the neck.…”
Section: Innovations In Recent Years Extended Deep Plane Rhytidectomymentioning
confidence: 99%
“…39,41 Cadaveric studies have shown that a more vertical pull avoids the distraction and dehiscence of the midline platysma commonly associated with a more superolateral vector of pull. 32 While previous rhytidectomy techniques describe releasing the retaining ligaments of the face and neck, the MACS vertical facelift only undermines a limited skin flap and, instead, uses purse-string sutures that are woven into the SMAS tissues (►Fig. 6).…”
Section: Vertical Liftmentioning
confidence: 99%